THE IMPACT OF FORESTRY SECTOR PERFORMANCE ON ECONOMIC INCOME GROWTH: A SOCIAL ACCOUNTING APPROACH - Ulya, Nur Arifatul; Yunardy, Syafrul (Journal of Indonesian Economy and Business, 2009)
Framework for Socio-economic Accounting System or the Social Accounting Matrix (SAM) states that the distribution of income received by each production factor specifiedin terms of economic sector concerned and called the factorial income distribution. Value added generated from the sum of total wages and salary plus capital income. Total of value added showed gross domestic product (GDP). Impact of Indonesias forestry sector performance can be measured by knowing its contribution to economic income growth.This paper discusses the impact of output growth in the forestry sector to factor income growth using Socio-economic Accounting System or the Social Accounting Matrix (SAM) approach. The impact of forestry sector production growth can be used to measure economic growth. Accounting multiplier is used to calculate the impact of output growth in the forestry sector to factor income growth in the year 2000 until the year 2005. Forestry sector for 5 years (2000-2005) gave a positive contribution to income growth. There are 16 economic sectors contributes positively to the factor income. Decrease in income growth occurred only on one factor of production, which are; Laborship,Leadership, Administration, Military, Professionals Recipients of Wages & Salaries in the Village. Forestry sector as a whole increases income growth of 104.64 percent during theyears 2000-2005.Keywords: accounting multiplier, production factor, SAM, value added